EVALUASI IMPLEMENTASI KEBIJAKAN DESENTRALISASI PENGELOLAAN HUTAN PRODUKSI - Sulistya Ekawati (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2013)
Production forest management has been decentralized by the Central Government to the Regency regarding Regulation No. 38/2007. After nearly twelve years of decentralization, deforestation in forest production showed the highest rate compared to other forest areas. This indicates that the policy is not effective. This study aims to evaluate the implementation of decentralization policy on production forests management. The study was conductedin Rokan Hulu and Pelalawan Regencies (RiauProvince),East Kutai and West Kutai Regencies (East Kalimantan Province). The collected data were analyzed with content analysis of existing legislation product and descriptive qualitative.The study results showed that: portion of the authority of forest management by local government (Regency) that represented by the existing production forest are aisquitelarge (47.16%), but based on existing legislation, the authority of the management of production forests by the the regency is less meaningful. Management of production forests have not been fully transfered from central government to localgovernments;some of the valuable economic powers still heldby the Central Government. Decentralisation of forest area utilization fermits through the HKm, HTR and Village Forest and the establishment of KPH is requiredto be more clarified and improved.